Research on Observation and Literature of Gui Pi Tang Treating Insomnia - Teoh, Zhi Yi (2015)
Insomnia is a sleeping disorder that interferes with daily activities which the person is difficulty falling asleep or staying asleep at night according to Nei Jing. Gui Pi Tang, as the formula for Spleen and Heart deficiency syndrome of insomnia which it is origin from “Ji Sheng Fang”. The objective of this project is to study the research on literature and observation of Gui Pi Tang treating insomnia in conjunction with previous academic writings as well as clinical observations. There were only 5 patients taken for the observation after confirmed that they are qualified the PSQI test with Heart and Spleen deficiency syndrome of insomnia and is advised to take 3g of Gui Pi Tang daily in the morning. Throughout the observation study of Gui Pi Tang, it shows that it is a potential formula which is effective in the treatment of insomnia.